Can or should we assess the growth impacts of climate protection? - Karen Pittel (EconPol Forum, 2023)
Predicting long-run growth effects of decarbonization is subject to high uncertainty. Awareness of limitations of growth forecasts should be raised. Scientific communication should aim at forecasts being misused in the political debate. Comparative analysis of growth effects can have value for policy design. A focus on absolute limits to growth can potentially be detrimental to decarbonization.
Keywords: 330